To the problem of diagnosis hematologic malignancies in elderly and senile - N. V. Khlevnaya; N. V. Ivanova (Кубанский научный медицинский вестник, 2016)
The article analyzed 43 cases of hematological diseases identified in patients with middle and old age, were treated in the regional hospital for war veterans. We discuss the identification of the most typical symptoms of various blood diseases, diagnostic difficulties and the algorithm of differential diagnosis. The study revealed the clinical features of hematological malignancies in the elderly.